2010
DOI: 10.1111/j.1556-4029.2009.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural, Unexpected Deaths: Reliability of a Presumptive Diagnosis*

Abstract: We retrospectively analyzed 100 deaths because of suspicions and concerns expressed by the family. We compared the preautopsy cause of death, as determined by a thorough review of the clinical data and circumstances, to the autopsy-derived cause of death. In the majority (91/100), the preautopsy and postautopsy proximate causes of death were in agreement. In 9%, the autopsy provided information that resulted in a proximate cause of death different than anticipated. In four instances, the manner of death also w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Despite modern imaging techniques, the autopsy along with all information available coming from the medical history, scene survey and circumstances of the death, is still considered the gold standard for determining the cause and manner of death. 18 The risk of misclassification is high when a cause/manner of death is not supplemented with data from autopsy and scene survey. A retrospective study on death certificates found that 34% of the cases had no proximate or a totally wrong cause/manner of death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite modern imaging techniques, the autopsy along with all information available coming from the medical history, scene survey and circumstances of the death, is still considered the gold standard for determining the cause and manner of death. 18 The risk of misclassification is high when a cause/manner of death is not supplemented with data from autopsy and scene survey. A retrospective study on death certificates found that 34% of the cases had no proximate or a totally wrong cause/manner of death.…”
Section: Discussionmentioning
confidence: 99%
“…23 Unfortunately the majority of trauma and violent deaths are still certified without an autopsy because of cost containment and increased confidence in modern imaging techniques. 18,21,26,27 Therefore, misdiagnoses as well as misinterpretation of medical findings are inevitable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, asymptomatic patients who may be infected with prions, or patients showing early but unreported clinical signs recorded with other more common causes of death (in particular sudden deaths, e.g., stroke or heart failure) represent a potential risk route of exposure of prion‐infected human material into anatomical research laboratories. The accuracy of death certificates and reliability of presumptive diagnosis in natural unexpected deaths reveal up to one‐third of recorded causes of death may be incorrect (Nielsen et al, ; Gill and Scordi‐Bello, ). The discrepancy between death certificate recorded cause of death and actual cause of death may have prompted the falling use of autopsy and pathological examination to be reversed (Roulson et al, ).…”
Section: Incidence and Disease Surveillancementioning
confidence: 99%
“…When a medical examiner or coroner (ME/C) is contacted, typically when a death is not due to natural causes, accuracy of death certificate information increases but remains imperfect . Manner of death (MOD) on death certificates is categorized as natural (i.e., when the body ceases to function of its own accord) or external/not natural (i.e., accident, suicide, homicide, undetermined).…”
mentioning
confidence: 99%